Flouting Maxims in “Wonder Woman“ Movie - Esra Juniati Op.Sunggu; Afriana Afriana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This research was made based on the number of people making mistakes in communicating in the social environment. Some errors in communication often result in ambiguity, due to the delivery of unclear information. Related to the topic the researcher made the research that analyze the flouting maxims in Wonder Woman movie and find the reason why the characters flouted the maxims by using the theory of Grice (1975). This research used qualitative descriptive method by Sudaryanto (2015) to analyze data. The results of the research showed that there were 12 data which were flouting maxims namely 1 data flouting maxim of quality, 2 data flouting maxim quantity, 2 data flouting maxim manner and 7 data were flouting maxim relations. The conclusion based on the results of this research is that all the characters in Wonder Woman movie was flouted all of the maxims, it can be seen from the result of analyzed the data, especially in the main character. The most frequently flouting maxim is maxim relation. Keywords: Communication, Cooperative Principle, Flouting Maxim.